PENGARUH KEMAMPUAN MEMBACA KITAB KUNING TERHADAP KETERAMPILAN BERBICARA BAHASA ARAB - Almannah Wassalwa; Anisatul Mardiyah (Lahjah Arabiyah: Jurnal Bahasa Arab dan Pendidikan Bahasa Arab, 2021)
This research is The Effect of Reading Ability (Mastery) Kitab Kuning on Arabic speaking skills in Ma'had Aly Marhalah Ula women's class. In this study, the researcher aims to determine whether or not there is an effect on reading ability in speaking Arabic. This research method uses quantitative research methods. From the results of calculations combined with the literature review, the ability to read the yellow book affects speaking skills in Arabic can be seen by it, both from a theoretical and empirical point of view. The results of the calculated data value were obtained by the number 0.416 after being consulted into the moving value coefficient between 0.400 - 0.599, which showed that it has a moderate category.